2023
DOI: 10.3390/jpm13121690
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia: Beyond the Narrative Review—The Point of View of Emergency Physicians and Medico-Legal Considerations

Gabriele Savioli,
Iride Francesca Ceresa,
Gaia Bavestrello Piccini
et al.

Abstract: Hypothermia is a widespread condition all over the world, with a high risk of mortality in pre-hospital and in-hospital settings when it is not promptly and adequately treated. In this review, we aim to describe the main specificities of the diagnosis and treatment of hypothermia through consideration of the physiological changes that occur in hypothermic patients. Hypothermia can occur due to unfavorable environmental conditions as well as internal causes, such as pathological states that result in reduced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Lunze et al in their systematic review found global case fatality rates associated with neonatal hypothermia ranging from 8.5% to as high as 52% [ 3 ] while another study in Malawi recorded a higher rate of mortality associated with hypothermia [ 23 ]. Although it is difficult to document the direct contribution of hypothermia to deaths in these patients, it is well known that hypothermia can alter general metabolism in the neonate, predispose to hypoglycemia, increase oxygen consumption at the initial stages, depresses respiration, and have adverse effects on the functions of the central nervous system [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lunze et al in their systematic review found global case fatality rates associated with neonatal hypothermia ranging from 8.5% to as high as 52% [ 3 ] while another study in Malawi recorded a higher rate of mortality associated with hypothermia [ 23 ]. Although it is difficult to document the direct contribution of hypothermia to deaths in these patients, it is well known that hypothermia can alter general metabolism in the neonate, predispose to hypoglycemia, increase oxygen consumption at the initial stages, depresses respiration, and have adverse effects on the functions of the central nervous system [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%